1977
DOI: 10.1111/j.1545-5300.1977.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Transactional Style Deviance in the TAT's of Parents of Schizophrenics

Abstract: Parents of schizophrenics show more transactional style deviance in diverse situations than do other parents. In a sample of families of nonschizophrenic outpatient adolescents, a manual for scoring such deviance on stories told for seven TAT cards was developed. This scoring system was shown to be composed of six meaningful factors. When this system was applied to the TAT's of parents of offspring with a variety of psychiatric diagnoses, a total deviance score did not discriminate among the parents. High scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 20 publications
4
90
1
Order By: Relevance
“…We have been able to observe this in our studies in which the stimulus material has been either a standardized communication conflict situation (CCS), or the TAT (18,38). Other research groups as well have found similar results (63,(67)(68)(69)72). Parents' egocentric communication may, of * This point of view assumes that individuals have a limited attention capacity.…”
Section: R Rundsupporting
confidence: 87%
See 1 more Smart Citation
“…We have been able to observe this in our studies in which the stimulus material has been either a standardized communication conflict situation (CCS), or the TAT (18,38). Other research groups as well have found similar results (63,(67)(68)(69)72). Parents' egocentric communication may, of * This point of view assumes that individuals have a limited attention capacity.…”
Section: R Rundsupporting
confidence: 87%
“…Egocentricity (18,67,68) as well as various forms of fragmentation and disruptive speech, closure problems, and certain other language anomalies (18,39,69,70), seem to particularly be more prominent in the communication between parents of schizophrenics, than between the parents of normal people. This is true at least for a sub-group of schizophrenics (70).…”
Section: The Environmental Explanatory Modelmentioning
confidence: 96%
“…The strength of the association was assessed using Kendall's tau c = -0.42, p < 0.032. High CD was defined as r>60 on factor 2 or 6 on Jones (1977) TAT measure.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Our experience with families containing a schizophrenic shows that communication in these cases is very disturbed in that it is not clear and unambiguous, but vague, ambiguous, con fused, inconsistent and incongruous. From the long list of verbal and non-verbal com munication problems we will simply men tion here disqualifications, 'pseudo-acknowl edgement' (a difference of opinion presented as agreement), contradictory messages, para doxical injunctions (two incongruous mes sages imposed at different levels of logic), inability to maintain and develop a focus of attention in time, indirect strategies (tension deviated from the field of transaction in question), inconsistencies between verbal content and non-verbal elements , We have also found that, in seriously disturbed families containing a schizophren ic, intolerance of autonomy and differentia tion of the various members of the family is never openly put into words, but every incli nation towards autonomy is made to disap pear by well-known psychotic transactions such as pseudo-mutuality, perceptual de fence, and an unshared focus of attention [Fivaz et al, 1979], These communication dysfunctions have been described by many authors and we can mention only a few major publications here: Wynne et al [1963,1977]; Singer et al [1965Singer et al [ , 1966Singer et al [ , 1978; Morris and Wynne [1965]; Mishler and Waxier [1968]; Kauf mann [1972,1984]; Goldstein and Rodnick [1975]; Jacob [1975]; Wild et al [1975]; Jones [1977]; Doane [1978]; Cosnier [1981].…”
Section: Can Thementioning
confidence: 99%
“…We propose to add to the vari able EE the concept of 'communication de viance' [Singer andWynne. 1966, 1978], or 'transactional style deviance' [Jones. 1977].…”
Section: Can Thementioning
confidence: 99%